Investigating impacts from topsoil stockpile height on soil microbial communities - Fischer, Ashley; Singh, Jay P.; Van Hamme, Jonathan; Bottos, Eric; Fraser, Lauchlan H. (Frontiers in Microbiomes, 2025)
Mining activities are often severely disruptive to the landscape, and a significant barrier to reclamation following mining operations is the lack of quality topsoil. This project addresses knowledge gaps in the industry by exploring the compositional nature of topsoil stockpiles and their ability to facilitate post-mining revegetation after long-term storage. To do this, we conducted a microbial profiling of two topsoil stockpiles in the interior of British Columbia, Canada. Both stockpiles show depleted soil quality and significant changes compared to reference soils. Notably, there were declines in microbial diversity and significant shifts in community structure with increasing stockpile depths in one of the stockpiles. These results highlight the influence of topsoil-stockpile height on microbial communities in the soil, which ultimately influences the success of restoration. This research can help the industry to optimize restoration and expedite recovery in their mine-closure practices and provides insights into the general structure of the microbiome existing across a gradient in severely disturbed mining soils.